PERBEDAAN AGRESIVITAS PENGUMUMAN LABA TRIWULANAN PADA PERUSAHAAN YANG MENCAPAI TARGET LABA DENGAN PERUSAHAAN YANG TIDAK MENCAPAI TARGET LABA - Desspa Ayu Pusparatna; Indira Januarti (Diponegoro Journal of Accounting, 2015)
This study aims to examine empirically whether there are differences in the aggressiveness of quarterly earnings announcements on companies that meet earnings target with companies that not meet earnings target. This study used secondary data taken from quarterly financial statements I, II, and III manufacture companies that listed in Indonesia Stock Exchange for years 2013-2014. This study used purposive sampling method. The amount of data being analyzed as many as 65 companies for each quarter for a total of as much data as 390 companies over two years. Data analysis includes descriptive statistics, analysis of cross tabulation (crosstab), normality test, and Mann-Whitney U test. Analyze data used IBM SPSS 20 software. Based on this study revealed that there were differences in the aggressiveness of quarterly earnings announcements on companies that meet earnings target with companies that not meet earnings target. Then, there were differences in the method of earnings management on companies that meet earnings target with companies that not meet earnings target. Companies that meet earnings target tend to use real earnings management method and companies that not meet earnings target tend to use accrual earnings management method.